A scoping review on community mobilisation for maternal and child health in sub-Saharan Africa: Impact on empowerment. Issue 3 (4th March 2019) - Beck, Dana C.; Munro-Kramer, Michelle L.; Lori, Jody R.
ABSTRACT: This review integrates evidence on community mobilisation (CM) for maternal and child health in sub-Saharan Africa (SSA) to identify the impact on empowerment. For the purposes of this review we use the following definition of CM: 'a capacity-building process through which community members, groups or organizations plan, carry out and evaluate activities on a participatory and sustained basis to improve their health and other conditions, either on their own initiative or stimulated by others', [Howard-Grabman, L., Storti, C., Hummer, P., Pooler, B., & Geneva: USAID (2007). Demystifying community mobilization: An effective strategy to improve maternal and newborn health . Retrieved from http://pdf.usaid.gov/pdf_docs/pnadi338.pdf, p. 5]. A scoping review was chosen to conduct a search and analysis of the literature due to the broad, complex nature of the topic. The search yielded 136 articles, and 19 met the inclusion criteria. This review illustrates CM as an important research process for engaging the community, ensuring that interventions are meeting the needs of the community, take context into account and are sustainable. Community mobilisation was associated with positive behaviour change and/or health outcomes. However, community mobilisation was not defined or operationalised consistently among the identified studies. Empowerment was also not defined, measured, or reported on in the articles. This review provides recommendations for the reporting of CM and its influence on empowerment in communities in sub-Saharan Africa.